National versus Trinitarian cacao hybrids in Ecuador: which is less infested by sap pests and which is less damaged by pod pests - Chirinos, Dorys T.; Castro, Rossana; Sánchez-Mora, Fernando David; Castro-Olaya, Jessenia; Mero Peñarrieta, Christina; Morán, Patricia; García Cruzatty, Luz C. (Frontiers in Agronomy, 2025)
Cacao (Theobroma cacao L.) is a tropical crop in high global demand. Ecuador is a significant producer and exporter of cacao where, there are several fine aroma cacao cultivars (type Nacional) and CCN51 (Trinitarian origin) in which the damages caused by pests in those genetic materials have so far been little evaluated. The objective of this research was to estimate the populations of sap pests and the damage caused to the pods in some genetic materials of cacao. This research was conducted during April 2022 - March 2023 in a 2160 m2 lot, planted in random blocks with four replicates and six families resulting from crosses: F1: L26-H64xL11-H19, F2: L26-H64xL21, F3: CCN-51xCCN-51, F4: L26-H64xCCN-51, F5: L21-H38xEET-103 y F6: L21-H38xL21-H38. Populations of Toxoptera aurantii, Planococcus sp., and Selenothrips rubrocintus were evaluated during the dry and rainy seasons. Damage to the pods was measured from S. rubrocintus and from Hemiptera species. Family F1 (National type) was the least infested by sap pests and showed moderate damage to the pods, while family F6 (National type) was the most infested. The dry season favored aphids, mealybugs and thrips, and damaged pods by S. rubrocintus. In the rainy season, the damaged pods from hemipterans was greater. To our knowledge, Leptoglossus zonatus and Guayaquilla gracillicornis are reported for the first time causing damage to cacao. Since one family of National type (F1) was less attacked by pests coupled with high yields, this fine aromatic cacao could represent a promising genetic material for the production of Ecuadorian cacao.